Estimating the Public Health and Economic Impact of Immunisation with Nirsevimab or Maternal Immunisation for the Prevention of RSV-Related Outcomes Over Infants’ First RSV Season in the UK - Mersha Chetty; Paul Costello; Benjamin Yarnoff; Robert Musci; Mehdi Ghemmouri (Infectious Diseases and Therapy)
Abstract Introduction Respiratory syncytial virus (RSV) poses a significant health burden on infants, particularly during their first RSV season. Immunoprophylactic strategies, such as the administration of nirsevimab, a long-acting monoclonal antibody, have been developed to prevent RSV lower respiratory tract disease (LRTD). This study evaluated the public health and economic impact of nirsevimab or maternal immunisation (MI) compared with standard of practice (SoP) in the United Kingdom (UK). Methods A static decision-analytic model was employed to track the UK birth cohort during their first RSV season. The model incorporated UK-specific data on costs, epidemiology and healthcare resource utilisation. Three strategies were compared: historical SoP (pre-September 2024), universal immunisation with nirsevimab and MI. Outcomes measured included RSV-related primary care (PC) visits, accident and emergency (AE) visits, hospitalisations, intensive care unit (ICU) admissions and deaths. The model also considered the impact of recurrent wheezing episodes, all-cause LRTD hospitalisations and non-medically attended RSV-LRTDs. Results Under the current SoP, RSV was estimated to cause 375,154 total health events and 24,360 RSV-LRTD hospitalisations (including ICU admissions) annually, resulting in an economic burden of £252 million. Universal immunisation with nirsevimab could prevent 208,691 total health events and 16,664 hospitalisations (including ICU admissions) and reduce costs by £105.7 million. MI showed a reduction in RSV-related outcomes but was less effective than nirsevimab, especially in preventing hospitalisations and ICU admissions or protecting infants born outside the RSV season. Conclusions Universal immunisation with nirsevimab for all infants during their first RSV season could significantly reduce both the health and economic burden of RSV in the UK. This strategy is more effective than MI, particularly in reducing severe RSV outcomes and protecting infants born outside the RSV season, thus offering substantial benefits across the infant population.